2021
DOI: 10.1007/s11250-021-02845-6
|View full text |Cite
|
Sign up to set email alerts
|

Dairy farm-workers’ knowledge of factors responsible for culling and mortality in the Eastern Cape Province, South Africa

Abstract: Milk serves as a significant source of protein for many families and aids in combating food insecurity. However, the demand for milk and milk-related products far exceeds the supply. The objective of the study was to evaluate dairy farm-workers’ knowledge of factors responsible for culling and mortality of dairy cows in the Eastern Cape Province. Data was collected from 106 dairy farm-workers using a questionnaire. Any correctly answered question by the majority amounted to a point and a zero for incorrectly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The dairy industry continues to be a male-dominated space in South Africa. The predominance of males (61.9%) in this study is similar to the 60% of males reported in a recent study in the same Eastern Cape province but in a different region (Diniso and Jaja, 2021 ). However, a knowledge, attitudes, and practices study on milk-borne zoonosis conducted in Ethiopia reported a low 35.7% male representation (Mandefero and Yeshibelay, 2018 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The dairy industry continues to be a male-dominated space in South Africa. The predominance of males (61.9%) in this study is similar to the 60% of males reported in a recent study in the same Eastern Cape province but in a different region (Diniso and Jaja, 2021 ). However, a knowledge, attitudes, and practices study on milk-borne zoonosis conducted in Ethiopia reported a low 35.7% male representation (Mandefero and Yeshibelay, 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, most participants were aged between 26 and 35 years, which is not significantly different from the 21-30 years reported in previous studies (Diniso and Jaja, 2021 ). This age is regarded as fit and healthy for several dairy farm activities.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…1 In South Africa, there has been a steady growth of 4.8% in 2018 and 3.0% in 2017. 2 This growth rate succeeds the 2.2% world milk production growth rate experienced in 2015, however there was a slight 0.1% drop in growth rate in 2016. 1 There is an expected production of 1077 million tonnes of milk by 2050.…”
Section: Introductionmentioning
confidence: 61%
“…4 In Ethiopia, the population is estimated to exceed 140 million by 2025 thus putting pressure on an already struggling food production industry including the dairy industry. 2 In fact, in previous years, overall demand for milk and milk-related products in Ethiopia far exceeded the supply as such per capita consumption of milk has been lower than 20 litres compared to the global 100 litres. Apart from milk yield concerns, in most developing African countries with escalating population growth, there is an on-going challenge of producing high quality milk i.e., low somatic cell count and high butterfat and other minerals content.…”
Section: Introductionmentioning
confidence: 99%